Successfully achieving target weight loss influences subsequent maintenance of lower weight and dropout from treatment. (16th October 2014) - Yamada, Tomohide; Hara, Kazuo; Svensson, Akiko Kishi; Shojima, Nobuhiro; Hosoe, Jun; Iwasaki, Minaka; Yamauchi, Toshimasa; Kadowaki, Takashi
<x xml:space="preserve">Abstract</x> Objectives The influence of the amount and rate of weight loss on subsequently regaining weight and dropout from treatment in severely obese patients targeting 5% weight loss was investigated. Methods A total of 120 consecutive hospital patients with severe obesity (BMI: 42 ± 9 kg/m2) participated in an inpatient program targeting 5% weight loss that involved goal setting, charting weight four times daily, and diet and exercise. They were followed after discharge to assess subsequent regaining of weight and dropout. Results Mean weight loss was 4.9 ± 2.4% after a mean of 19 days in the hospital, and 43% of the patients achieved the target weight loss (>5%). Over the median 2‐year follow‐up period, greater than 5% in‐hospital weight loss was associated with a significantly lower risk of regaining weight after adjustment for various factors (>5% to ≤7% loss: hazard ratio 0.30 [0.11‐0.85] for regaining all of the lost weight and 0.32 [0.13‐0.78] for regaining half of the lost weight). No significant relation between the amount or rate of weight loss and dropout from subsequent outpatient treatment was seen. Conclusions Successfully achieving the target weight loss in a comprehensive program predicts subsequent maintenance of lower weight without increasing the risk of dropout. Successful in‐hospital weight loss might increase the motivation of obese patients.